Gambaran Pemanfaatan Poliklinik Kesehatan Desa Sebagai Perpanjangan Tangan Puskesmas di Kabpaten Purbalingga - Ekowati, Wahyu; Kamaluddin, Ridlwan; Triyanto, Endang (Jurnal Keperawatan Soedirman, 2008)
Mother mortality inIndonesiain the year 1997 is 334 per 100.000 birth of life, while death of baby same as AKB in the year gyrate 52 per 1000. In the effort drawing near service of health to society and also strive generalization of service of effort and health push society independence for healthy life, government through Department Health specify wisdom to place energy nurse of countryside midwife below/under doctor leader of puskesmas. To improve degree of health of society isn't it alert countryside movement which one of [the] the program of is development of Polindes become Polyclinic Health Of Countryside. InSub-ProvinceofPurbalinggafrom 133 existing Polindes, 78 among others have become Polyclinic Health of Countryside which the was place of spread over inSub-ProvinceofPurbalingga.Intention of this research is to know the image of exploiting of Polyclinic Health of Countryside as extention of hand of Puskesmas inSub-ProvinceofPurbalingga. This Research is descriptive research by using sampling purposive that is counted 30 Polyclinics Health of Countryside with criterion reside in Sub-Province of Purbalingga and have stood more than 6 months. Data the taken is amount of amount of society visits to medicinize to Polindes and society visit to medicinize to Polyclinic Health of Countryside. Data Visit which in taking is last 3 months data.Result which in getting mean of amount of society visits to tired Polindes 36 people per month, while for the Polyclinic of Health of tired Countryside 58 people per month. Existence of improvement of society visit amount and benefit to exploiting of Polyclinic Health of Countryside as extention of hand of Puskesmas that is happened the make-up